Work Engagement : A Systematic Literature Review and Bibliometric Analysis - Nurrosidah, Ali; Sopiah, Sopiah (Jurnal Etnik: Ekonomi-Teknik, 2022)
Discussion related to work engagement is important for studied in human resource management. Purpose of this research for review studies that discuss work engagement related with other topics such as leadership styles, HRM practice and organizational commitment. Data used a total of 30 articles indexed by Scopus for the 2019-2022 period. This study method uses systematic literature review (PRISMA) and technique analysis with analysis bibliometric using the VOSviewer software. Visualized analysis results through Co-Authorship Co- Occurrence , a quote article most identified through 10 groups citation highest. Showing that work engagement relates with other topics are leadership styles, HRM practice, organizational commitment, behavior psychology and systems work. Studies literature this expected becomes reference for next study regarding work engagement and other relevant variables